Meningkatkan Kinerja Karyawan: Dapatkah Iklim Organisasi dan Servant Leadership mempengaruhinya? - Yoke Sanasa; Fifi Oktaviani (LPPM Universitas Banten jaya, 2022)
The development of an organization, especially in the world of hospitality, cannot be separated from the behavior of its members. The role of employees in developing the organization is fundamental in obtaining organizational success. The purpose of this study is to investigate how to improve employee performance in the hospitality industry. This research was conducted at Marabella Hotel & SPA Anyer. The sample used is as many as 65 people. While the analysis tool uses SmartPLS version 3. The results of this study, first, the organizational climate has a positive and significant influence in improving employee performance. Second, servant leadership has a positive and significant influence in improving employee performance.